Fishery and population dynamics of sacred chank Turbinella pyrum (=Xancus pyrum Linnaeus, 1758) off Kayalpattinam in the Gulf of Mannar - Jagadis, I.; Syda Rao, G.; Joshi, K. K.; Kandan, P. (Indian Journal of Fisheries, 2011)
The fishery and population dynamics of the sacred chank exploited by bottom-set gillnet off Kayalpattinam, Gulf of Mannar were studied during 2004-2006. The size/weight range was between 80-290 mm / 60 to 1600 g. The age of the chanks was estimated to be 20+ years and it reaches 94/135, 154/453, 197/833 and 227 mm /1195 g in 1, 2, 3 and 4th year of life. The lengthâ€“weight relationship of (L-W) of Turbinella pyrum was W = 0.001728 * L (2.47087), lengthâ€“maximum shell diameter (L-MSD) was W = 0.0011749 * MSD (2.851393). The VBGF parameters estimated are Lâˆ = 306.1 mm, K = 0.33 yr-1 and Wâˆ = 2.5 kg. Estimated total mortality, natural mortality and the fishing mortality are 1.6913 yr-1, 0.45909 yr-1 and 1.2322 yr-1 respectively. From the estimates arrived at the fishing pressure on chanks in the fishing ground is evident and about 30% reduction from the present effort of 5,943 units operated from Kayalpattinam is required to sustain the stock and return to the maximum sustainable yield (MSY) of 48-5t.